SuperBetter : a revolutionary approach to getting stronger, happier, braver, and more resilient* - McGonigal, Jane (Penguin Press, 2015)
A renowned game designer describes how she recovered from a debilitating concussion by turning her therapeutic process into a digital game that became the subject of a major NIH research study.